Trends in Radical Surgical Treatment Methods for Breast Malignancies in China: A Multicenter 10-Year Retrospective Study. (7th August 2015) - Zhang, Bai-Lin; Sivasubramaniam, Priya G.; Zhang, Qian; Wang, Jing; Zhang, Bin; Gao, Ji-Dong; Tang, Zhong-Hua; Chen, Guo-Ji; Xie, Xiao-Ming; Wang, Zhongzhao; Yang, Hong-Jian; He, Jian-Jun; et al.
Abstract: Background: Incidence rates of breast cancer continue to rise in the People's Republic of China. The purpose of this study was to describe Chinese trends in radical surgical modalities and influential imaging and demographic factors for breast malignancies. Materials and Methods: This study was a hospital-based, multicenter, 10-year (1999–2008), retrospective study. Descriptive statistical tests were used to illustrate information regarding radical surgical trends for the treatment of breast malignancies. Chi-square tests were used to assess effect of demographic factors in addition to imaging and pathological data on the specific surgical method. Results: A total of 4, 211 patients were enrolled in the survey. Among them, 3, 335 patients with stage 0 to stage III disease undergoing mastectomy or breast-conserving surgery (BCS) were included in the final analysis. The rate of BCS increased from 1.53% in 1999 to 11.88% in 2008. The rate of mastectomy declined over this time period, from 98.47% in 1999 to 88.12% in 2008, with increasing use of diagnostic imaging methods and pathological biopsies. A significantly greater percentage of patients with office work, high education levels, unmarried status, younger age, and early pathological stages preferred BCS compared with mastectomy. Conclusion: Rates of mastectomy in China remain elevated due to diagnosis at higher stages; however, because of increased use of diagnostic imaging, improvement of biopsy methods, and patient education, rates of less invasive lumpectomy are increasing and rates of mastectomy have decreased in China. Implications for Practice: In this study, 4, 211 cases were collected from 1999 to 2008 through a multicenter retrospective study of varying geographic and socioeconomic areas to illustrate trends of surgeries in the People's Republic of China. The correlations between demographic and tumor characteristics and among methods of surgical treatment were explored. This study shows that the rate of breast-conserving surgery (BCS) increased and the rate of mastectomy declined over this time period with increasing use of diagnostic imaging methods and pathological biopsies. Patients with office work, high education levels, unmarried status, younger age, and early pathological stages preferred BCS compared with mastectomy in China. Abstract : The purpose of this study was to describe Chinese trends in radical surgical modalities and influential imaging and demographic factors for breast malignancies. Rates of mastectomy in the People's Republic of China remain elevated due to diagnosis at higher stages; however, because of increased use of diagnostic imaging, improvement of biopsy methods, and patient education, rates of less invasive lumpectomy are increasing and rates of mastectomy have decreased in China.